Estudios de corrientes Río Amazonas - Current studies Amazon River (My University, 1920)
The map shows the studies of the Amazon River, Iquitos and surrounding areas.

El plano muestra los estudios de corrientes Río Amazonas, Iquitos y cercanías
Iquitos y cercanías
Keywords: Incluye las escalas de Corrientes de Río Amazonas; Iquitos; y cercanías.; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps